Evolution of Metastasis Study Models toward Metastasis‐On‐A‐Chip: The Ultimate Model?. Issue 14 (11th March 2021) - Ruiz‐Espigares, Jesús; Nieto, Daniel; Moroni, Lorenzo; Jiménez, Gema; Marchal, Juan Antonio
Abstract: For decades, several attempts have been made to obtain a mimetic model for the study of metastasis, the reason of most of deaths caused by cancer, in order to solve the unknown phenomena surrounding this disease. To better understand this cellular dissemination process, more realistic models are needed that are capable of faithfully recreating the entire and essential tumor microenvironment (TME). Thus, new tools known as tumor‐on‐a‐chip and metastasis‐on‐a‐chip have been recently proposed. These tools incorporate microfluidic systems and small culture chambers where TME can be faithfully modeled thanks to 3D bioprinting. In this work, a literature review has been developed about the different phases of metastasis, the remaining unknowns and the use of new models to study this disease. The aim is to provide a global vision of the current panorama and the great potential that these systems have for in vitro translational research on the molecular basis of the pathology. In addition, these models will allow progress toward a personalized medicine, generating chips from patient samples that mimic the original tumor and the metastatic process to perform a precise pharmacological screening by establishing the most appropriate treatment protocol. Abstract : This work provides a new vision about the paradigms of metastasis, as well as the evolution of study models for its resolution. Tumor‐on‐a‐chip are extensively described, being discussed whether they have the capacity to synthesize minimal functional units that recapitulate the biological processes involved in metastasis. The main problems to solve for translation to the clinical arena are also highlighted.